INTEGRASI SUSTAINABLE DEVELOPMENT GOAL 14 MELALUI PRAKTIK BLUE ACCOUNTING PADA PT. PELNI (PERSERO) - Junardi Junardi (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the integration of Sustainable Development Goal (SDG) 14: Life Below Water into accounting practices and sustainability reporting of PT PELNI (Persero). The research employed a qualitative descriptive approach with a case study method using content analysis of annual and sustainability reports from 2019 to 2023. The findings reveal that PT PELNI implemented various initiatives such as mangrove planting, coral reef restoration, ship waste management, emission reduction, and coastal community education. These programs can be classified as blue expenses aligned with SDG 14 indicators and the Global Reporting Initiative (GRI) standards. Although there has been significant progress in narrative disclosure, transparency, and quantification of activities over time, the classification of blue expenses has not been explicitly presented in official reports. The evaluation shows that narrative integration and data transparency are adequate, while financial classification and indicator mapping remain partial. This study recommends the development of a blue expense classification system, integration of SDG–GRI–cost–output mapping into sustainability reporting, and improvement of data auditability. Therefore, PT PELNI has the potential to become a pioneer in applying blue accounting within Indonesia’s maritime sector.